Workshop Artikel Digital Untuk Pariwisata Berkelanjutan: Mengintegrasi Budaya Literasi, Green School, Dan Teknologi - Setiawi, Agustina Purnami; Mau, Stefanus Dwi Istiavan; Sabawaly, Diana Reby; Janga, Adelbertus Umbu (CV. Global Cendekia Inti, 2024)
The workshop “Digital Articles for Sustainable Tourism: Integrating Literacy Culture, Green School, and Technology” at SMKS Bakti Luhur Tambolaka aims to enhance teachers' digital literacy and article writing skills, with a focus on sustainable tourism. This activity is designed to equip teachers with an understanding of the essential role of digital literacy in disseminating information on sustainability issues, particularly in the tourism sector. In the digital era, this literacy is increasingly relevant in helping teachers convey messages about the importance of environmental preservation through responsible tourism practices. In addition to digital literacy, the workshop introduces the Green School concept, an educational approach focused on environmental sustainability. This concept emphasizes reducing paper usage and promotes technology-based learning to support eco-friendly educational processes. Through the Green School concept, teachers are encouraged to integrate digital technology into their daily teaching, including publishing educational articles on sustainability on school blogs or social media. Thus, teachers are not only trained in writing but are also taught how to leverage digital platforms as interactive learning media. The workshop consists of material sessions, writing practice, and group discussions. Teachers are divided into groups to write articles related to sustainable tourism. They practice crafting messages about eco-friendly tourism into informative and engaging digital articles. The results of this activity show that the teachers not only gained technical skills in digital writing but were also able to create content that promotes environmental awareness among students. With these skills, the teachers are expected to become agents of change, spreading the values of sustainable tourism and environmentally friendly education to students and the wider community, aligning with the needs of education in the digital era.